Value Chain Analysis of Rattan in Nepal - Chowdhary, Chhote Lal; Dhutta, I. C. (Nepal Journal of Multidisciplinary Research, 2021)
This study highlights the existing situations of production, value addition, marketing and uses of rattan cane in Nepal. Rattan enterprises exist as a small and medium enterprise (SME) within and outside the community forest user groups. The study was designed based on the exploratory research and was carried out in Kailali and Bardiya districts. The main objective was to assess the constraints and opportunities of rattan cane enterprise as well as design business solutions. Systematic random sampling method was followed to take the sampling of CFUGs, households and small and medium enterprises. Primary data was collected through focus group discussions, key informants interview, direct observations, open-ended questionnaires, and inventory of growing stock. Similarly, secondary data was collected from progress reports, Forest Operational Plans, audit reports and records of community forest user groups and Division Forest Offices. Sampling design was ascertained representing sampling units of rattan managed Community Forest User Groups and processing industries. The questionnaire survey was conducted to executive committee members of 8 Community Forest User Groups, 526 households and 12 rattan processing industries/ enterprises. Direct observation and interaction with CFUG and entrepreneurs were another major source of information. The quantitative data was analyzed using SPSS 20 and Microsoft Excel software tools. The identified major constraints concerning the selected value chains were: absence of detailed resource inventory in the approved Forest Operational Plans; inadequate knowledge about resource management, poor capacity to incorporate environmental policy concerns, weak business competitiveness, insufficient information about market and poor marketing knowledge. The study also identified a number of opportunities both in the community as well as enterprise perspective. For example, resource potential and monetary benefits to the community people; contribution in community development, involvement of service providers in forest resource management; employment generation and leveraging ecosystem services. The findings suggested technical and business solutions for the effective value chain of rattan cane.